Pharmacological Analysis of the Anti-epileptic Mechanisms of Fenfluramine in scn1a Mutant Zebrafish - Sourbron, Jo; Smolders, Ilse; de Witte, Peter; Lagae, Lieven (Frontiers in Pharmacology, 2017)
Dravet syndrome (DS) is a genetic encephalopathy that is characterized by severe seizures and prominent co-morbidities (e.g. physical, intellectual disabilities). More than 85% of the DS patients carry an SCN1A mutation (sodium channel, voltage gated, type I alpha subunit). Although numerous anti-epileptic drugs (AEDs) have entered the market since 1990, these drugs often fail to adequately control seizures in DS patients. Nonetheless, current clinical data shows significant seizure reduction in DS patients treated with the serotonergic (5-hydroxytryptamine, 5-HT) drug fenfluramine (FA). Recent preclinical research confirmed the anti-epileptiform activity of FA in homozygous scn1a mutant zebrafish (ZF) larvae that mimic DS well. Here we explored the anti-epileptiform mechanisms of FA by investigating whether selective agonists/antagonists of specific receptor subtypes were able to counteract the FA-induced inhibition of seizures and abnormal brain discharges observed in the scn1a mutants. We show that antagonists of 5-HT1D and 5-HT2C receptor subtypes were able to do so (LY 310762 and SB 242084, respectively), but notably, a 5-HT2A-antagonist (ketanserin) was not. In addition, exploring further the mechanism of action of FA beyond its serotonergic profile, we found that the anti-epileptiform brain activity of FA was significantly abolished when it was administered in combination with a σ1-agonist (PRE 084). Our study therefore provides the first evidence of an involvement of the σ1 receptor in the mechanism of FA. We further show that the level of some neurotransmitters (i.e. dopamine (DOP) and noradrenaline (NAD)) in head homogenates was altered after FA treatment, whereas ɣ-aminobutyric acid (GABA) and glutamate (GLUT) levels were not. Of interest, NAD-decreasing drugs have been employed successfully in the treatment of neurological diseases; including epilepsy and this effect could contribute to the therapeutic effect of the compound. In summary, we hypothesize that the anti-epileptiform activity of FA not only originates from its 5-HT1D- and 5-HT2C-agonism, but likely also from its ability to block σ1 receptors. These findings will help in better understanding the pharmacological profile of compounds that is critical for their applicability in the treatment of DS and possibly also other drug-resistant epilepsies.